ANALISA FREE CASH FLOW DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN UTANG (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI INDONESIA) - Mawardi, M. Cholid (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2014)
The objectives of this study are : 1) to know the influence of free cash flow to debt policy in the company that have low investment opportunity set, 2) to know the influence of free cash flow to the debt in the big company which have low investment opportunity set, 3) to know the influence of managerial ownership to the debt policy in the small company. This study employs debt as dependent variable and free cash flow and managerial ownership as independent variable. The sample of this study is 36 Indonesia companies listed in the Indonesia Stock Exchange from 2010 to 2013. The results indicate that the companies with low investment opportunity set and high free cash flow tend to use debt to finance companies operation. And managerial ownership has positive correlation to the debt in the small company. It proves that managerial ownership has ability to minimalize agency cost.